THE PROBLEM OF ARTICLES AND THE CATEGORY OF DEFINITENESS IN ENGLISH AND UZBEK LANGUAGES - Abdullaev Nuritdin Bakhridinovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article examines the category of definiteness and the use of articles in English and Uzbek languages from a comparative perspective. English uses a grammatical system of articles to express definiteness and indefiniteness, whereas Uzbek lacks articles and conveys similar meanings through contextual and lexical means. The study highlights the main differences between the two languages and discusses common difficulties faced by Uzbek learners of English.